Analisis Perencanaan dan Pengendalian Biaya Penjualan Produk Pada Usaha Mikro Kecil dan Menengah (UMKM) pada Konveksi Praha Profesional Studio - Sandi Alam; Fitrawansyah Fitrawansyah; Listya Ningrum (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Analysis of planning and controlling product sales costs in micro, small and medium enterprises (MSMEs). The location of this research was carried out at the Praha Professional Studio Convection which is located on Jalan Tikukur 1, Karawang Indah Housing, Block B, No 10, Rt/008, Rw/013, Karawang Kulon Village, West Karawang District, Karawang Regency. The method used in this study is a descriptive method with a qualitative approach with the aim of obtaining in-depth data, a data that contains real meaning and produces an accurate picture. Data collection techniques used are triangulation techniques, namely observation, interviews and documentation. The results of this study indicate that the calculation of the cost of products carried out by Praha Professional Studio Convection is not correct, due to the wrong calculation process and the classification of costs is not in accordance with the concept of cost accounting. Therefore, with the recommendation of the process of calculating the cost of goods in this study, Praha Professional Studio Convection can apply it in order to obtain cost information as a good cost planning and facilitate management in controlling costs.